(untitled) (Research, Society and Development, 2022)
The species Coffea arabica and Coffea canephora, arabica and conilon, respectively, are the most widely used by coffee roasters worldwide. This work aimed to trace the physicochemical profile of blends made with Arabica and Conilon coffee subjected to different roasting conditions. Eleven blends were prepared, according to a complete 23 factorial design, in different concentrations of arabica and conilon, temperature and roasting time. The blends were roasted, ground, physico chemically analyzed and the results submitted to statistical analysis. All blends classified as fine roast, showed low mass loss and good yield. Density was higher for blends with higher concentration of conilon. pH and color were the parameters most influenced by the degree of roasting. The values of moisture, total soluble solids, aqueous extract, caffeine, and lipids were in accordance with what is required by legislation. It was observed that the experiments elaborated with 31.25% arabica coffee, roasted at 170 ºC for 12 min, showed good results, in relation to the visual and physicochemical aspects, indicating that it can be a standard of blend adopted by the roasting industries. of coffee.